Migration and Deconstruction of the Costa Rican Imaginary in “Abbott y Costello,” by Sergio Ramírez - Vargas Vargas, José Ángel (2018)
This paper analyzes the issue of migration in the story “Abbott y Costello,” from Flores Oscuras. Migration is studied as the main chronotope of the text, with its organic and dialogical character, and it is linked to the construction and deconstruction discourse of the Costa Rican imaginary. Sergio Ramírez, in his narrations, fictionalizes different topics of the social life and the historical reality of Central America. He is interested in a strong referentiality in each country, based on an exercise of representing issues such as power, poverty, war, migration, economy and culture.